Analysis of the potential for organizational interoperability improvement in local government - Dias, G.P. (2010)
In this artic le we present an analysis of the potential for organizational interoperability in a cluster of local government in Portugal consisting of the City Council, the Land Registry Office and the Tax Office of Portalegre. Based on an exhaustive survey of procedures we identified the direct and indirect interactions between these three agencies and measured the rate of organizational interoperability and the potential for improving organizational interoperability. These two quantities were defined within the scope of the research work that is described in the article. We also present a set of proposals that will, in the short and medium term, significantly improve organizational interoperability in the cluster. The results obtained allow affirming the relevance of organizational interoperability in the context of e-government initiatives.